Global burden of childhood Burkitt lymphoma (1990–2021): epidemiological trends, regional disparities, and projections for 2035 from the Global Burden of Disease Study - Ma, Guoqian; Hou, Changyu; Li, Yuan; Jia, Fan (Frontiers in Medicine, 2025)
BackgroundBurkitt lymphoma (BL) is a highly aggressive pediatric B-cell lymphoma with marked geographic heterogeneity. Up-to-date global estimates are needed to inform prevention and care.MethodsWe analyzed Global Burden of Disease (GBD) 2021 data to estimate incidence, mortality, and disability-adjusted life years (DALYs) for childhood BL (0–14 years) from 1990 to 2021 across 204 countries/territories, stratified by sex, age, region, and Sociodemographic Index (SDI). Trends were summarized using joinpoint annual percent change and estimated annual percentage change (EAPC). Bayesian age-period-cohort models projected the burden to 2035.FindingsIn 2021, there were 4,083 incident BL cases globally [95% uncertainty interval (UI) 2,688–5,171]. The global incidence rate was 0.20 per 100,000 (95% UI 0.13–0.26) versus 0.16 per 100,000 (95% UI 0.10–0.23) in 1990. Burden varied substantially by development level: the low-SDI region had the highest incidence rate (0.44 per 100,000, 95% UI 0.26–0.59), mortality rate (0.43 per 100,000, 95% UI 0.25–0.58), and DALY rate (36.19 per 100,000, 95% UI 21.00–48.64). High-SDI regions showed lower mortality rates and evidence of declines, consistent with broader access to timely diagnosis, multi-agent chemotherapy, and supportive care. By 2035, the incidence rate is expected to reach 0.15 (95% CI 0.11–0.19) per 100,000, the mortality rate to 0.10 (95% CI 0.07–0.13) per 100,000, and the DALY rate to 8.21 (95% CI 5.98–10.43) per 100,000.InterpretationGlobal BL rates appear broadly stable, with pronounced inequities concentrated in low-SDI settings. Apparent improvements are heterogeneous, not universal, and are most evident in high-SDI regions where treatment and supportive care are widely available. Projections to 2035 suggest modest declines in global rates, contingent on sustained malaria control and expanded access to diagnosis and curative therapy in high-burden regions. Targeted investments linking infection control with pediatric oncology capacity are required to reduce the global burden of childhood BL.